Analysis the Impact of Islamic Leadership on the Islamic Work Ethics of Pegadaian Syariah Employees - Ahdi Zidan Laiqkafana; Rozikan (Journal of Islamic Economic and Business Research, 2023)
The high work ethic of employees is one of the positive behaviors expected by the company. This is because the work ethic is the key to the company's success in competing with other companies. One of the keys to improving an employee's work ethic is having a leader who has influence in changing the behavior of his employees. The purpose of this study was to find out and analyze the challenges faced by Islamic Pawnshop leaders in improving the Islamic work ethic of employees at Pegadaian Syariah in the Special Region of Yogyakarta (DIY). This research used a descriptive qualitative method. In this study, the interview method was used on the subject (employee) to obtain valid data to detect the effect of using the theory effectively. The results of this study indicate that applying Islamic Leadership can improve the Islamic work ethic in Pegadaian Syariah in the Special Region of Yogyakarta and positively impact creating an Islamic work environment and strengthening employee performance. In its implementation, there are several challenges in lack of understanding and awareness, the environment, and compliance with Sharia principles. For this reason, managers of Pegadaian Syariah should provide regular training and outreach to employees so that the Islamic work ethic can be maintained properly.